'Spurious Articles': the purchases of the Department of Science and Art from the Hamilton Palace sale of 1882. (22nd December 2014) - Maxwell, Christopher
Abstract: By the penultimate decade of the nineteenth century, the Dukes of Hamilton, premier peers of Scotland, had amassed a superb collection of fine and decorative art. However, in 1882, with over £1 million of debt, William, 12th Duke of Hamilton (1845–1895) and his astute Commissioner, Henry Padwick (1804–1879), exploited an apparent loophole in the Duke's deeds of entail which enabled them to consign the renowned ducal art collection to Christie Manson & Wood. The auction occurred just months before the British government introduced the Settled Land Act 1882, which thereafter enabled the sale of entailed property and opened the flood gates to a deluge of country house sales which radically transformed the dynamics of the British art market. Following a second round of sales in 1919, the family's principal seat, Hamilton Palace, ten miles south of Glasgow, was demolished. Many of the most significant items from both the 1882 and 1919 sales are now in the great museums, galleries and libraries of the world or in important private collections. This article considers the success of the Department of Science and Art in furnishing its London, Edinburgh and Dublin museums with acquisitions from the landmark sale of 1882, and identifies further objects with a Hamilton Palace provenance that have subsequently entered their collections.